2018
DOI: 10.5552/drind.2018.1725
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Fiber Morphology, and Kraft Pulping of Bracken Stalks (Pteridium aquilinum (L.) Kuhn)

Abstract: Chemical Composition, Fiber Morphology, and Kraft Pulping of Bracken Stalks (Pteridium aquilinum (L.) Kuhn) Kemijski sastav, morfologija vlakana i sulfatni postupak proizvodnje celuloze od stabljika paprati (Pteridium aquilinum (L.) Kuhn)Original scientifi c paper • Izvorni znanstveni rad ABSTRACT • In this study, kraft, kraft-NaBH 4 , and kraft-KBH 4 pulp and paper properties of the bracken stalks (Pteridium aquilinum (L.) Kuhn) were determined. Also, the chemical composition and fi ber properties of bracken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Generally, lignin is an undesirable polymer, and its removal during pulping requires high amounts of energy and chemicals (Cao et al 2014). In addition, higher lignin percentages in raw materials reduce the chemical pulp yield and the fiber strength (Gülsoy and Şimşir 2018). Notably, the results revealed that the branches from both species had higher lignin contents compared with the stemwood.…”
Section: Comparison Of Chemical Properties Of Stem and Branch Woodmentioning
confidence: 96%
“…Generally, lignin is an undesirable polymer, and its removal during pulping requires high amounts of energy and chemicals (Cao et al 2014). In addition, higher lignin percentages in raw materials reduce the chemical pulp yield and the fiber strength (Gülsoy and Şimşir 2018). Notably, the results revealed that the branches from both species had higher lignin contents compared with the stemwood.…”
Section: Comparison Of Chemical Properties Of Stem and Branch Woodmentioning
confidence: 96%
“…The higher an SR value is, the longer, thinner, and more flexible the fibers are considered to be, and subsequently, the stronger the tearing resistance of the paper sheet is expected to be (Ogbonnaya et al 1997;Nasser et al 2015). An optimal SR value range between 95 and 120 or between 55 to 75 for softwood and hardwood pulps, respectively, is recommended (Tofanica et al 2011;Rudi et al 2016;Gülsoy and Şimşir 2018). However, a non-wood plant source is considered sufficient for papermaking processes if the SR value is less than 70 and higher than 33 (Saeed et al 2017a).…”
Section: Morphological Indices and Papermaking Potentialmentioning
confidence: 99%
“…The FC index is related to the individual elasticity of fibers and has a positive effect on the interfibrillar bonding behaviour of fibers, and eventually on the tensile and burst strength properties. Plant fibers can be classified as highly rigid fibers (an FC less than 30) through high elastic fibers (an FC greater than 75) (Tofanica et al 2011;Gülsoy and Şimşir 2018). A higher rigidity of fiber has a negative influence on the mechanical strength properties of the resulting paper and provide porous papers with lower resistance (Nasser et al 2015;Saeed et al 2017a).…”
Section: Morphological Indices and Papermaking Potentialmentioning
confidence: 99%
See 2 more Smart Citations